APPENDIX B: ELEMENTS OF POSITIVE STRATEGY. NEW INITIATIVES FOR INDUSTRTYACTION (Tufts Archival Research Center, 2007)
Report summarizing current and prospective Tobacco Institute programs addressing such issues as fire safety education, adult decisions and teenage smoking, industry support of Damon Runyon-Walter Winchell Cancer Fund, tobacco means jobs, working with the handicapped, teenage pregnancy, and health science education. Concludes an inventory of industry activity in these areas would be beneficial as a frame of reference for tobacco companies, as well as a measure to improve the industry's public image.